Locations and Predictive Factors of Hypertrophic Pachymeningitis in Otitis Media With Antineutrophil Cytoplasmic Antigen-Associated Vasculitis. Issue 8 (4th September 2022) - Morita, Yuka; Kitazawa, Meiko; Yagi, Chihiro; Takahashi, Kuniyuki; Ohshima, Shinsuke; Yamagishi, Tatsuya; Izumi, Shuji; Horii, Arata
Abstract : Objective: To determine the locations and predictive factors of hypertrophic pachymeningitis (HP), a serious central complication of otitis media with antineutrophil cytoplasmic antigen-associated vasculitis (OMAAV). Study Design: Retrospective study. Setting: University hospital. Patients: Thirty-six patients with OMAAV underwent contrast-enhanced magnetic resonance imaging (CE-MRI) of the brain, of whom 18 and 18 had or did not have HP, respectively. Main Outcome Measures: The location of HP lesions, which were detected as dural thickening on CE-MRI, was reviewed. Clinical characteristics, laboratory data, and audiometric data before treatment were correlated with the occurrence of HP. Results: HP lesions were most frequently observed in the middle cranial fossa, followed by the internal auditory meatus, tentorium cerebelli, and posterior cranial fossa, which were adjacent to the middle ear primary lesion. Headache was more frequently observed in patients with HP than without HP. The neutrophil-to-lymphocyte ratio (NLR) of the HP (+) group (median, 3.91; interquartile range, 2.50–6.06) was higher than that of the HP (−) group (median, 2.40; interquartile range, 2.01–3.03). The area under the receiver operating characteristic curve for the NLR was 0.741. An NLR of 3.46 had the highest sensitivity (61.1%) and specificity (94.4%) for predicting HP. Other markers of systemic inflammation and comorbidities of systemic diseases were not different between the groups. Conclusions: HP may not be a systemic manifestation of OMAAV but may be related to local lesions in the adjacent brain. A high NLR may be a predictive factor for comorbid HP. Therefore, CE-MRI should be considered for patients with a high NLR.